2011
DOI: 10.1111/j.1471-0528.2011.02906.x
|View full text |Cite
|
Sign up to set email alerts
|

Early versus late epidural analgesia and risk on instrumental delivery in nulliparous women: a systematic review

Abstract: Background The optimal timing of epidural analgesia during labour and delivery has been a controversial issue.Objective Review of the literature regarding the relation between the timing of epidural analgesia and the rate of caesarean or instrumental vaginal deliveries.Search strategy Pubmed, Embase and the Cochrane Library were searched for articles published until 31 July 2010.Selection criteria Studies were selected in which the effects of early latent phase (defined as a cervical dilatation of 3 cm or less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 27 publications
0
16
1
Order By: Relevance
“…This is in contrast to the study by Wang et al 6 More recently, a systematic review of 6 studies (N=15,399) showed no increased risk of cesarean (pooled risk ratio 1.02 95% CI 0.96-1.08) or instrumental (pooled risk ratio 0.96 95% CI 0.89-1.05) delivery for women receiving early epidural (defined as 3 cm or less) in comparison with late epidural placement. 7 Wassen et al8 suggested that routine epidural analgesia may increase the rate of operative deliveries, however the difference between vaginal (difference: 4.5% (95%CI: -1.6, 10.6)) or via cesarean (3.6% (95%CI: -3.1, 10.3) did not reach statistical significance. Also, adverse labor outcomes such as incidence of shoulder dystocia, postpartum hemorrhage, manual placenta extraction, and third/fourth degree perineal lacerations; and neonatal outcomes were no different.…”
Section: Discussionmentioning
confidence: 97%
“…This is in contrast to the study by Wang et al 6 More recently, a systematic review of 6 studies (N=15,399) showed no increased risk of cesarean (pooled risk ratio 1.02 95% CI 0.96-1.08) or instrumental (pooled risk ratio 0.96 95% CI 0.89-1.05) delivery for women receiving early epidural (defined as 3 cm or less) in comparison with late epidural placement. 7 Wassen et al8 suggested that routine epidural analgesia may increase the rate of operative deliveries, however the difference between vaginal (difference: 4.5% (95%CI: -1.6, 10.6)) or via cesarean (3.6% (95%CI: -3.1, 10.3) did not reach statistical significance. Also, adverse labor outcomes such as incidence of shoulder dystocia, postpartum hemorrhage, manual placenta extraction, and third/fourth degree perineal lacerations; and neonatal outcomes were no different.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, these investigators observed no effects of early labor analgesia on operative vaginal or cesarean birth rates. More recently, a systematic review of 6 studies (N=15,399) showed no increased risk of cesarean (pooled risk ratio 1.02 95% CI 0.96–1.08) or instrumental (pooled risk ratio 0.96 95% CI 0.89–1.05) delivery for women receiving early epidural (defined as 3 cm or less) in comparison with late epidural placement 32 .…”
Section: Fallaciesmentioning
confidence: 99%
“…More recently, a systematic review of six studies (n = 15 399) showed no increased risk of caesarean (pooled risk ratio 1.02, 95% CI 0.96-1.08) or instrumental (pooled risk ratio 0.96, 95% CI 0.89-1.05) delivery for women receiving early epidural (defined as dilatation ≤3 cm) in comparison with late epidural placement. 32 The aforementioned findings have led ACOG to conclude that,…”
Section: Fallaciesmentioning
confidence: 99%
“…A 2011 meta-analysis of five randomized trials and one retrospective cohort study (n = 14,836) indicated that early administration of neuraxial analgesia (cervical dilation ≤ 3 cm) did not increase the incidence of Cesarean sections (RR 1.02, 95% CI 0.96 to 1.08) or instrumental deliveries (RR 0.96, 95% CI 0.89 to 1.05) in comparison to later administration (cervical dilation ≥ 4 cm) [44]. …”
Section: The Timing Of Neuraxial Analgesia and Labor Outcomementioning
confidence: 99%